“Denmark As A Prison of Life” In Shakespeare’s Hamlet (A Semiotic Approach In Literature) - Hadiyanto Hadiyanto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
AbstractHamlet is one of the well-known Shakespeare’s drama highlighting betrayal, murder, and revenge. This paper discusses Shakespeare’s Hamlet by studying signs in the text with a semiotic approach in literature. “Denmark is prison” is chosen to be the primary signifier in Shakespeare’s Hamlet that can represent all the main characters’ feeling and perspective in the text such as Hamlet, Claudius, Getrude, Hamlet’s ghostly father, Polonius, Ophelia, Laertes, Horatio, Fortinbras, Rosencrantz, and Guildenstern. They feel Denmark is a prison for their heart. Prison is a symbol of an unpleasant place where the dwellers do not feel happy since they cannot live freely. The characters’ own feeling leads them to live in Denmark unhappily. The story climax is that all of the main characters at the end of the story suffer or die tragically. Key words: Hamlet, signifier, prison, betrayal, murder